2022
DOI: 10.3389/fnut.2022.851255
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Ameliorates Inflammation in Acute Lung Injury via NF-κB/Nlrp3 Signaling Pathway

Abstract: The inflammatory response is the key pathophysiological character of acute lung injury (ALI). Berberine (BBR), a natural quaternary ammonium alkaloid, plays a functional role in anti-inflammation both in vitro and in vivo. However, the underlying mechanism between BBR and ALI has not been expounded. Here, we found that BBR improved the permeability of pulmonary and repressed the inflammatory factors in the lipopolysaccharides (LPSs)-induced ALI model. We demonstrated that BBR could suppress the expression of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Berberine exerts an influential role in suppressing inflammation by amplifying the NF-κB signaling pathway [ 38 ]. It was shown that induction of PI3K/AKT leads to signaling and translocation downstream of the NF-κB trans-transcription factor [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Berberine exerts an influential role in suppressing inflammation by amplifying the NF-κB signaling pathway [ 38 ]. It was shown that induction of PI3K/AKT leads to signaling and translocation downstream of the NF-κB trans-transcription factor [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear factor-κB (NF-κB) signaling pathway is a classical inflammatory signaling pathway that closely interacts with the NLRP3 inflammasome to drive the production of inflammatory mediators 54 , 55 . Compared to the control, silica treatment significantly increased the phosphorylation-mediated activation of IκBα and NF-κB p65, and these effects were inhibited by MCC950 (Figure 7 A).…”
Section: Resultsmentioning
confidence: 99%
“…At the biomolecular level, BBR causes a reduction of inflammatory damage in the animal organism by activating inflammatory vesicle NLRP3, which binds to ASC. Further, the expression of inflammatory factors is decreased, such as IL-6, IL-18, IL-10, TNF-α, and IL-1β ( 14 , 48 ). IL-6 activates the downstream JAK2.…”
Section: Discussionmentioning
confidence: 99%